Disaster management : building dynamic capabilities through cross-sector partnerships: Case study of Finnish SMEs in disaster market - Mahmoodi, Kosar (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
Disasters caused by nature or created by man are becoming more frequent and growing more severe than ever before. Hence there is a great need for effective disaster management. The challenges faced by third and public sector are not successfully tackled without the involvement of private sector. Private companies produce solutions to prevent, manage the crisis, and rebuild in areas where natural disasters or conflicts occurs. The participation of Finnish SMEs in disaster market has been very low even though Finland is remarkable with its offerings. The product or the service itself alone does not guarantee business opportunities in disaster market. Therefore, there is a need to form cross-sector partnerships. Cross-sector partnership alliances are ideal in disaster market since it enables companies to develop their resources and capabilities with participating organizations. The purpose of this thesis was to understand how dynamic capabilities can be created through cross-sector partnerships in high-velocity disaster markets. Dynamic capabilities are the highest form of capability a company can have. The study combined literature from disaster management, cross-sector partnerships and dynamic capabilities. This thesis was conducted by using qualitative research method in data collection. The main empirical data was collected through semi-structure interviews with Finnish SMEs that have wide experience in disaster market operations and commercial cross-sector partnerships. The key findings of this study shows that cross-sector partnerships, both successful and unsuccessful ones, help private companies to develop their dynamic capabilities. Reconfiguration, leveraging, learning, and creative integration are four modes of dynamic capabilities that are beneficial for disaster management. In addition, this study reveals that private companies do not fully acknowledge the positive impact of cross-sector partnerships on business operations. The collaboration more often lead to new resource configurations and new innovative solutions. According to the findings, involving locals has a very effective impact on the success in the disaster market. Furthermore, it was discovered that private companies may need to make changes into their processes in order to adapt to the environment and effectively manage the disaster. This research provides great insight into disaster market from Finnish perspective and during the research, several new research needs were discovered.